Basket guiding device - WANG YAO; ZHANG JIANFENG; LIU JINGLONG; HUANG HAIYAN; WANG SHIPENG; FANG JIE; LU CHUAN; YANG SUIYI (2018)
The utility model provides a basket guiding device, this basket guiding device include base, a stopper body, the 2nd stopper body and guiding groove structure, and the guiding groove structure includes the guiding groove of a plurality of parallel ranges, it sets up on the upper surface of base to walk abreast to a stopper body and the 2nd stopper body interval, and wherein, a stopper body lies inthe edge of base upper surface one side, a stopper body's upper surface includes that the guiding groove structure sets up in the second area near the 2nd stopper body's first region and the second area of keeping away from the 2nd stopper body, and wherein, the orientation that the guiding groove extends is the same with a stopper body and the 2nd stopper body's array orientation, the bottom ofa stopper body's upper surface, the 2nd stopper body's upper surface and guiding groove is in same horizontal plane. Use the utility model provides a basket guiding device can make the guide card process between the basket of